ANALISIS FUNGSI PELAYANAN KECAMATAN-KECAMATAN DI BAGIAN TIMUR KABUPATEN KONAWE SELATAN - Setiawan, Didi; Saenong, Zainuddin; Matoka, Ulfa (JURNAL EKONOMI UHO, 2016)
This research aims to: (1) identify and analyze the  services functions of  eastern of South Konawe Regency, (2) identify and analyze the degree of interaction between the district  in eastern of South Konawe. Methods of collecting data is documentation of secondary data for 2015 period.  The analyzed  data used  Schallogram and Gravity analysis. The results showed that the  Ranomeeto district  is in  first  hierarchy, besides that Konda district  in  the second. Konda and Moramo district  have broader  services and  reach  the three  of the seven districts in the eastern of South Konawe as  a result  more populous and close  distance.